HISTORICAL ROOTS OF NATIONAL VALUES (American Journal of Business Management, Economics and Banking, 2025)
The article highlights the historical roots of national and religious values, their role in society and human life. It is analyzed that national and universal values existed in interdependence, and that universal values, such as honesty, tolerance and justice, developed on the basis of national customs and traditions.